Neon ist ein Gas und hat zwei Ringe – Zur Trennung der makroskopischen und submikroskopischen Ebene des Periodensystems. Issue 6 (22nd August 2018) - Abels, Simone; Koliander, Brigitte; Plotz, Thomas; Heidinger, Christine
Translation abstract: Sometimes it is not made explicit to which level (macroscopic or submicroscopic) the topic being talked about during a chemical lesson should be assigned. Even in the learning materials used the levels are often mixed, for example in the periodic table of elements that are shown in textbooks. This can be a learning barrier for students. Illustrated by a case study some learning difficulties of students in learning the atomic structure with the help of such a periodic table of elements are shown. The use of two different periodic tables of elements is suggested to support the more explicit separation of the macroscopic and submicroscopic level.